The Influence of the Effectiveness of the Internal Audit Function and Organizational Culture on the Implementation of Internal Control and its Impact on Fraud Prevention in Regional General Hospitals in the West Java Region - Irawan, Nugrahadi Fajria; Winarningsih, Srihadi; Mubarrok, Ahmad Zakie (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
This research aims to determine how the effectiveness of the internal audit function and organizational culture influence fraud prevention through the implementation of internal control in the West Java Regional Regional Hospital. The factors tested in this research are the effectiveness of the internal audit function and organizational culture as independent variables, the implementation of internal control as a mediating variable, while fraud prevention as the dependent variable. The research method used is explanatory. The population in this study was all 57 hospitals in the West Java region. The sampling technique used was a probability sampling technique with a simple random sampling method, so that the research sample was all 41 hospitals in the West Java region. The analysis method used is Structural Equation ModelingÂ¬-Partial Least Square (SEM-PLS) using SmartPLS software. The research results show that the effectiveness of the internal audit function and organizational culture has a direct influence on the implementation of internal control, the effectiveness of the internal audit function and organizational culture has a direct influence on fraud prevention, the implementation of internal control has a direct influence on fraud prevention, as well as the effectiveness of the internal audit function and culture Organizations have an indirect influence on fraud prevention mediated by the implementation of internal controls.